Agresivitas Pajak Ditinjau dari Risiko Perusahaan, Likuiditas dan KAP Big Four - Firmansyah Firmansyah; Meutia Layli; Cyntha Mellia Febrina Utomo (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2022)
This study aims to find empirical evidence by analyzing the effect of corporate risk, liquidity, and Big Four Firm of Public Accountants variables on tax aggressiveness in basic and chemical manufacturing companies listed on the IDX for the 2016–2020 period. In this study, there were 24 manufacturing companies in the basic and chemical industry sectors listed on the IDX for the 2016 – 2020 period. The sampling technique was purposive sampling. The data was obtained from the official website of the Indonesia Stock Exchange. Testing the research hypothesis using multiple linear regression models. The purpose of this study is to understand the existence of any factors that affect tax aggressiveness. The results of this study indicate that the company's risk has a positive effect on tax aggressiveness. This shows that the higher the risk of the company, the higher the tax aggressiveness in the company, while the liquidity and Big Four Firm of Public Accountants variables do not affect tax aggressiveness. The company's risk of tax aggressiveness can reduce the value of trust in the community. The existence of external control, namely Big Four Firm of Public Accountants does not experience a significant difference.